Actin-Bundling Protein TRIOBP Forms Resilient Rootlets of Hair Cell Stereocilia That Are Essential for Hearing - Kitajiri, Shin-ichiro (2010)
Inner ear hair cells detect sound through deflection of mechanosensory stereocilia. Each stereocilium is supported by a paracrystalline array of parallel actin filaments that are packed more densely at the base, forming a rootlet extending into the cell body. The function of rootlets and the molecules responsible for their formation are unknown. We found that TRIOBP, a cytoskeleton-associated protein mutated in human hereditary deafness DFNB28, is localized to rootlets. In vitro, purified TRIOBP isoform 4 protein organizes actin filaments into uniquely dense bundles reminiscent of rootlets, but distinct from bundles formed by espin, an actin cross-linker in stereocilia. We generated mutant Triobp mice (Triobp(Δex8/Δex8)) that are profoundly deaf. Stereocilia of Triobp(Δex8/Δex8) mice develop normally, but fail to form rootlets and are easier to deflect and damage. Thus, F-actin bundling by TRIOBP provides durability and rigidity for normal mechanosensitivity of stereocilia and may contribute to resilient cytoskeletal structures elsewhere.